2007
DOI: 10.1161/01.str.0000257314.74853.2b
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pretreatment Blood Pressure With Tissue Plasminogen Activator-Induced Arterial Recanalization in Acute Ischemic Stroke

Abstract: Background and Purpose-Elevated systolic blood pressure (SBP) and lack of early vessel recanalization are predictors of poor outcome among patients with stroke treated with systemic tissue plasminogen activator (tPA). We aimed to evaluate the potential relationship between pretreatment SBP and tPA-induced recanalization. Methods-Consecutive patients with acute ischemic stroke resulting from intracranial artery occlusion were treated with standard intravenous tPA and assessed with 2-MHz transcranial Doppler for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 34 publications
3
86
2
Order By: Relevance
“…However, these unselected data suggest closer control of postthrombolysis systolic BP. Our findings are consistent with an intravenous thrombolysis study 31 and a rather large study in general stroke patients (nϭ1455) 32 but not with smaller studies (n Ͻ400). 33,34 In our study, BP was measured according to usual clinical practice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, these unselected data suggest closer control of postthrombolysis systolic BP. Our findings are consistent with an intravenous thrombolysis study 31 and a rather large study in general stroke patients (nϭ1455) 32 but not with smaller studies (n Ͻ400). 33,34 In our study, BP was measured according to usual clinical practice.…”
Section: Discussionsupporting
confidence: 89%
“…28 Vessel recanalization is an important predictor for outcome, 29 but complete vessel recanalization occurs in approximately 27% of patients treated with intravenous thrombolysis. 30,31 Therefore, our results cannot be explained simply by vessel recanalization.…”
Section: Discussionmentioning
confidence: 79%
“…These data are in line with the studies of randomized IVT trials that found high BP to be associated with SICH. [3][4][5][6][7] We found no interaction of baseline BP with IAT on SICH or other safety parameters, so IAT may be considered safe, independently of BP.…”
Section: Baseline Bp and Outcomementioning
confidence: 92%
“…It was recently reported that higher pretreatment blood pressure levels are associated with poor recanalization in patients with acute stroke treated with IV tissue plasminogen activator. 27 Patients with adequate collaterals do not need highly elevated perfusion pressures to protect the threatened field; in contrast, blood pressure elevations may increase collateral flow in passive pressure-dependent ischemic fields in patients with inadequate collateral. Early hypertension after ischemic stroke was associated with increased mortality.…”
Section: Resultsmentioning
confidence: 99%